Measuring Performance of International Joint Ventures - Geringer, J. Michael; Hebert, Louis (Journal of International Business Studies, 1991)
International joint ventures (IJVs) are increasing in frequency and strategic importance. However, efforts to identify variables associated with IJV performance have been constrained by disagreements regarding the comparability and reliability of alternative performance measures and methods. This study tests several hypotheses regarding the reliability and comparability of a range of objective and subjective measures of IJV performance, as well as evaluating the relative utility of different data collection approaches.